1986
DOI: 10.1007/bf02346052
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of photosynthetically active cyanobacteria in glutaraldehyde-crosslinked albumin matrix

Abstract: Summary. Cryoprotection was afforded to cells ofPhormidium luridum and Anacystis nidulans by preloading them with dimethyl sulphoxide and then performing the immobilization reaction in dimethyl sulphoxide-free medium. Compared with free cyanobacteria cells, matrix-immobilized cyanobacteria exhibit superior temperature tolerance and storage longevity of photoinduced electron transport, while their phycobiliproteins are better protected against thermal denaturation. Photosynthetically active Phormidium spheropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…It has been recognized that the carbohydrate investments of cells may contribute substantially to their resistance to air drying, and the entrapment of cells and enzymes in polysaccharide gels is an immobilization technique that has been applied extensively in different systems (203,427). Compared with free-living cyanobacterial cells, matriximmobilized cells exhibit superior temperature tolerance and storage longevity of photoinduced electron transport, and desiccation-sensitive proteins such as phycobiliproteins are more stable (273). Owing to the desiccation resistance and radiation resistance of Deinococcus (Micrococcus) radiodurans, it has been suggested that packets of dried cells could be used as a dosimeter for sterilizing doses of radiation (359).…”
Section: Po1tismentioning
confidence: 99%
“…It has been recognized that the carbohydrate investments of cells may contribute substantially to their resistance to air drying, and the entrapment of cells and enzymes in polysaccharide gels is an immobilization technique that has been applied extensively in different systems (203,427). Compared with free-living cyanobacterial cells, matriximmobilized cells exhibit superior temperature tolerance and storage longevity of photoinduced electron transport, and desiccation-sensitive proteins such as phycobiliproteins are more stable (273). Owing to the desiccation resistance and radiation resistance of Deinococcus (Micrococcus) radiodurans, it has been suggested that packets of dried cells could be used as a dosimeter for sterilizing doses of radiation (359).…”
Section: Po1tismentioning
confidence: 99%
“…The albumin-containing cryogels are of special interest, because different albumins (the class of water-soluble globular proteins 15 ) are, first, widely distributed in nature and thus readily available; and second, being biocompatible, are suitable for various biomedical applications. For instance, bovine serum albumin (BSA) was used for creating aldehyde-cross-linked spongy cryogel-type carriers of immobilized cells and organelles, 4,5,16,17 and ovalbumin (the albumin of the egg white) was the macromolecular precursor for producing wide-pore scaffolds for cell culturing. 8 In the latter case the cryogel preparation procedure was based on the approach 18 implying partial denaturation of protein globules induced by additives of chaotropic substances, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The key features of these gel matrices are their biocompatibility and, in principle, biodegradability [ 9 , 10 ]. Specific groups of the polypeptide- and protein-composed gels are those prepared in moderately-frozen systems via the so-called cryotropic gelation processes [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that result in the formation of proteinaceous cryogels (e.g., see [ 10 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]). Among the latter gel matrices of certain applied interest are biodegradable wide-porous cryogels based on individual blood proteins or their natural (plasma, serum, cell lysate) and artificial mixtures [ 10 , 11 , 22 , 23 , 24 , 25 , 31 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…(i) by the 3D coupling of the protein macromolecules with the aid of auxiliary cross-linking reagents added to the precursor solution directly prior to its cryogenic processing [ 10 , 11 , 22 , 23 , 24 , 25 , 29 , 30 , 31 , 34 ];…”
Section: Introductionmentioning
confidence: 99%